PENGARUH MODEL ROLE PLAYING TERHADAP HASIL BELAJAR IPS KELAS V DI SD - Putri, Ramadhani Aulya; Sugiyono, Sugiyono; Sabri, Tahmid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study purposed to analyze how much influence of the role playing model has on the learning outcomes on Social Sciences of the fifth grade students on public elementary school 66 Pontianak City. The method was experimental method with the form of Quasi Experimental Design types of Nonequivalent Control Group Design. The population in the study of all fifth grade students of Pontianak Kota 66 Elementary School, amounting to 65 people, took the sample using simple random sampling technique so that the sample was VA class as the experimental class and VB as the control class. Data collection techniques were measurement techniques, with data collection tools is a test of multiple choice students amounted to 50 questions. Based on data analysis, the result of the average post-test experimental class= 71.36 and average post-test result of the control class= 62.43. The results of hypothesis testing (t-test) obtained t count 2.255 and t table 2.007 (significant level (Î±) = 5% and dk = 53) which means tcount > ttable, then Ha is accepted. This means there was a significant influence on applying the role playing model. From the calculation of Effect Size (d) obtained 0.62 (medium criteria). The role playing model influences the learning outcomes of Social Sciences in class V of Elementary School 66 Pontianak City.Â Key words :Â Learning Outcomes, Role Playing, Sosial Sciene.Â